D’une hétérotopie à l’autre où le vagabondage au féminin (Jean Echenoz, Un an) - Jişa, Simona (Quêtes littéraires, 2014)
Jean Echenoz’s text presents Victoria’s story who runs away from Paris, believing that she has killed her lover. Her straying (that embraces the form of a relative deterritorialization in a Deleuzian sense) lasts one year and it is built up geographically upon a descent (more or less symbolical) to the South of France and, after that, she comes back to Paris and encloses the spatial and textual curl. From a spatial point of view, she turns into a heterotopia (Foucault) every place where she is located, fact that reflects her incapability of constituting a personal, intimate space. The railway stations, the trains, the hotels, the improvised houses of those with no fixed abode are turning, according to Marc Augé’s terminology, into a « non-lieux » that excludes human being. Her vagrancy is characterized through a continuous flight from police and people and through a continuous decrease of her standard of living and dignity. It’s not about a quest of oneself, but about a loss of oneself. Urged by a strong feeling of culpability, her vagrancy is a self-punishment that comes to an end when the concerns of her problems disappear and she finds out that her lover is alive.